The Videogame Industry Does Not Exist - Keogh, Brendan (The MIT Press, 2023)
The precarious reality of videogame production beyond the corporate blockbuster studios of North America.The videogame industry, we're invariably told, is a multibillion-dollar, high-tech business conducted by large corporations in North America, Europe, and East Asia. But, in reality, most videogames today are made by small clusters of people working on shoestring budgets, relying on existing, freely available software platforms, and hoping, often in vain, to rise to stardom—in short, people working like artists. Aiming squarely at this disconnect between perception and reality, The Videogame Industry Does Not Exist presents a more accurate and nuanced picture of how the vast majority of videogame-makers work.Drawing on insights from over 400 game developers, Brendan Keogh develops a new framework for understanding videogame production as a cultural field in all its complexity. Part-time hobbyists, aspirational students, client-facing contractors, struggling independents, artist collectives, and tightly knit local scenes—all have a place within this model. But proponents of non-commercial game-making don't exist in isolation; Keogh shows how they and their commercial counterparts are deeply interconnected and codependent in the field of videogame production. A cultural intervention, The Videogame Industry Does Not Exist challenges core assumptions about videogame production and reveals the diverse and precarious communities, identities, and approaches that make it a significant cultural practice.